An observer based robust state feedback control for active suspension system with adaptive compensation of nonlinear actuator - Vahid Mokhtari; Ali Akbarzadeh Kalat; Naeimeh Fakhr Shamloo (International Journal of Engineering Education, 2021)
In this paper, an observer based robust state feedback control strategy is proposed for a car suspension system with nonlinear actuator in order to moderate vertical motion of the body. At first, an adaptive inverse control is developed to overcome the nonlinearity of the actuator. Secondly, to cope with unavailability of some states of the system, a velocity observer is employed. Afterward, an observer based robust state feedback control is suggested for the system and robust stability of the overall control system is proved by Lyapunov theory. Efficiency and robustness of the proposed method is shown by comparing simulation results for the active and passive suspension system in the same road conditions.